PENGUKURAN TINGKAT PROFITABILITAS PERBANKAN SYARIAH INDONESIA DENGAN MENGGUNAKAN RASIO CAMEL PERIODE 2012-2016 - Jurnal Ilmiah Manajemen Universitas Putera Batam (Universitas Putera Batam, 2018)
This research measuring the profitability of Sharia banks Indonesia with using CAMEL ratio. The proxy of CAMEL ratio is CAR, NPF, NPM, BOPO and FDR variables. The object of reserach is Public Sharia banks has published Financial Statement period of 2012-2016 with amount 10 banks.Technical analysis of data used Multiple Regression. The result showed that CAR, NPF, NPM, BOPO and FDR had simultaneous effect of profitability (ROA) with R2 75,6% with significance level α = 0.05. CAR and BOPO have a negative and significantly effect on profitability ratios. While the NPM and FDR variables have a negative and significantly effect on the profitability, and NPF variable have no effect.